Does consumers’ involvement in e-commerce last-mile delivery change after COVID-19? An investigation on behavioural change, maintenance and habit formation - Wang, Xueqin (2023)
The COVID-19 pandemic accelerates e-commerce adoption, which naturally induces an expedited acceptance of innovative last-mile deliveries. Focusing on self-collection via parcel lockers, this study investigates consumers’ behavioural change, maintenance and habit formation related to e-commerce deliveries in response to the pandemic. We use a survey instrument for data collection (n = 500) and structural equation modelling for data analysis. Anchored on the risk–attitude–norm–ability–self-regulation (RANAS) framework, this study found that risk, attitude, norm, ability and self-regulation factors related to using the contactless shopping-delivery channel lead to the formation of self-collection habits, and that the formation process is fully mediated by consumers’ maintenance motivation to use the channel. Furthermore, consumers’ online shopping habit partially mediates the relationship between the maintenance motivation and self-collection habit formation. Additionally, model comparisons are conducted,revealing the differentiated habit formation processes. The findings contribute to a theoretical understanding of the formation of delivery habit as driven by the pandemic. Practical implications are also created which guide logistics and e-commerce operators’ interactions with consumers in the post-pandemic period.